Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Anggota Koperasi Kelurahan Merah Putih Candiroto Kecamatan Kendal Kabupaten Kendal (International Forum of Researchers and Lecturers, 2026)
This study aims to determine the effect of price and service quality on customer satisfaction of members of the Merah Putih Candiroto Village Cooperative, Kendal District, Kendal Regency. This study uses a quantitative approach, associative research type, with a sample of members of the Merah Putih Candiroto Village Cooperative, Kendal. The sampling method was carried out using a saturated sampling technique. The total sample in this study was 137 respondents. The variables in this study were independent variables: price and service quality, and the dependent variable: customer satisfaction of members of the Merah Putih Candiroto Village Cooperative, Kendal. Testing in this study used instrument testing, classical assumption testing, and hypothesis testing with multiple regression tests using SPSS Version 25. The results of this study indicate that partially the price has a positive and significant effect on customer satisfaction of members of the Merah Putih Village Cooperative, Candiroto, Kendal with a t-count of 3.418 greater than the t-table of 0.1678 and a significant value of 0.001 smaller than the significance level of 0.05. And the quality of service partially has a positive and significant effect on customer satisfaction of members of the Merah Putih Village Cooperative, Candiroto, Kendal with a t-count of 3.643 greater than the t-table of 0.1678 and a significant value of 0.000 smaller than the significance level of 0.05. Price and service quality simultaneously have a positive and significant effect on customer satisfaction of members of the Merah Putih Village Cooperative, Candiroto, Kendal, with F count of 715.041 greater than F table of 0.1678 with a significance of 0.000 smaller than the significance level of 0.05. The Adjusted R square result of 0.913 indicates that 91.3% of customer satisfaction of members of the Merah Putih Village Cooperative, Candiroto, Kendal, is influenced by price and service quality whose influence was tested in this study, while the remaining 8.7% is influenced by other variables not examined in this study.